THE RELATIONSHIP BETWEEN KNOWLEDGE AND THE BEHAVIOR OF HEIGHT WORKERS AT PT. X ON THE BINTARO XCHANGE II PROJECT IN 2023 - Hariyanti; Azizah Zen; Munaya Fauziah; Triana Srisantyorini (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
As Reported by the International Labour Organization (ILO), about 380,000 workers, or 13.7% of the 2.78 million workers, die from workplace accidents or occupational diseases each year. In addition, more than 374 million people are injured or sick each year. Data from the International Labour Organization (ILO) shows that every year around 380,000 workers or 13.7% of the 2.78 million workers die due to workplace accidents or occupational diseases. And more than 374 million people are injured, injured or fall ill each year as a result of accidents with workers. Types of analytical descriptive research with quantitative approaches and cross sectional study designs (potong lintang). Data gathering by lifting, analysis by chi square. The sampling technique uses the Total Sampling method. The population is the total of the 75 height workers in PT. X. According to the results of the analysis, there are 8 (10.7%) employees with less knowledge, 30 (40%) workers with sufficient knowledge and 37 (49.3%) employees with good knowledge. The age picture is known as 50 (66.7%) employees who are ≤ 40 years old and 25 (33.3%) workers who are > 40 years of age. The education picture is 16 (21.3%) people with an educated level of middle school and 59 (78.7%) people with a high school education. The behaviour picture is 38 (50.7%) workers with unsafe behavior and 37 (4.9%) people who have safe behaviors. The results of the bi-variant test on the independent variable relate to the dependent variable, covering the frequency of knowledge with a p value of 0.018, the age with a P value of 0.009, and education with the p value 0.004. Factors related to employee behavior are knowledge, age and education. A suggestion for PT. X to hold a socialization on K3 every month (potentially hazardous, full APD area or other K3 information through posters, banners or other information media).